Estimation and evaluation of iron reserves in the eastern area of Eileh1 mine, Razavi Khorasan province - Hamid Esmati Daroneh; Maryam Gholamzadeh (Journal of Economic Geology)
In the present study, we aimed to gain a comprehensive understanding of the Eileh 1 iron ore deposit located in Taybad City, Razavi Khorasan Province. A three-dimensional (3D) model was developed using specialized software, which incorporated lithological logs from boreholes, cross-sectional lithological profiles, and assay estimations covering the entire ore deposit area. The dominant lithology of the region consists of altered limestone and dolomite, as well as altered sediments, including sandstone, siltstone, and shale. To estimate the reserves, we employed both the classical inverse distance weighting (IDW) method and the geostatistical kriging method, tailored to the specific conditions of the ore deposit. Variogram analysis indicated that data values varied with distance and direction, revealing geometric anisotropy within the deposit. The maximum search radius in the direction of 0° azimuth was 42.6 meters, the average search radius at 90° azimuth was 10.6 meters, and the minimum search radius in the vertical direction (0° azimuth) was 32 meters. The dataset included topographic information and data from 177 boreholes, totaling 6,936 meters deep. Following geometric modeling and constructing a block model for the deposit, we estimated reserves for various iron-grade thresholds and compared the results of both methods. The findings indicate that the reserve estimates from the two methods were quite similar. While the inverse distance weighting method is recognized as one of the most accurate classical techniques for reserve estimation, the kriging method demonstrated greater precision and reliability. This is attributed to Kriging’s ability to account for the spatial structure of the deposit, its unbiased nature, and its lower estimation variance. The findings indicate that the reserve estimates from the two methods were quite similar. While the inverse distance weighting method is recognized as one of the most accurate classical techniques for reserve estimation, the kriging method demonstrated greater precision and reliability. This is attributed to Kriging’s ability to account for the spatial structure of the deposit, its unbiased nature, and its lower estimation variance.